2009
DOI: 10.1142/s1793830909000063
|View full text |Cite
|
Sign up to set email alerts
|

On the Pipage Rounding Algorithm for Submodular Function Maximization — A View From Discrete Convex Analysis

Abstract: We consider the problem of maximizing a nondecreasing submodular set function under a matroid constraint. Recently, Calinescu et al. (2007) proposed an elegant framework for the approximation of this problem, which is based on the pipage rounding technique by Ageev and Sviridenko (2004), and showed that this framework indeed yields a (1 − 1/e)-approximation algorithm for the class of submodular functions which are represented as the sum of weighted rank functions of matroids. This paper sheds a new light on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…It is noted that a similar statement is shown in Shioura [42] for a monotone M -concave function defined on 2 N ; we here extend the result to the case of non-monotone M -concave function defined on a subset of 2 N .…”
Section: -Convex Functionssupporting
confidence: 85%
See 1 more Smart Citation
“…It is noted that a similar statement is shown in Shioura [42] for a monotone M -concave function defined on 2 N ; we here extend the result to the case of non-monotone M -concave function defined on a subset of 2 N .…”
Section: -Convex Functionssupporting
confidence: 85%
“…If w(v) = 1 (v ∈ N ), then f is an ordinary rank function of the matroid (N, I). Every weighted rank function is a GS utility function [42]. 2…”
Section: Preliminariesmentioning
confidence: 99%
“…The maximization problem has also been studied for variants of submodular functions. Shioura [24] investigated the maximization of discrete convex functions. Soma et al [26] provided a (1 − 1/e)-approximation algorithm for maximizing a monotone lattice submodular function under a knapsack constraint.…”
Section: Related Workmentioning
confidence: 99%
“…Any DR-submodular function is lattice submodular; i.e., DR-submodularity is stronger than lattice submodularity. 1 The problem of maximizing DR-submodular functions over Z E naturally appears in the submodular welfare problem [16,24] and the budget allocation problem with decreasing influence probabilities [26]. Nevertheless, only a few studies have considered this problem.…”
mentioning
confidence: 99%
“…The applications of discrete convex analysis include economics, system analysis for electrical circuits, phylogenetic analysis, etc. Shioura [22] studied maximization of the sum of M ♮ -concave set functions subject to a matroid constraint. He showed that pipage rounding [2] can be explained from the viewpoint of discrete convexity.…”
Section: Related Workmentioning
confidence: 99%